Nanobiomaterials in hard tissue engineering : applications of nanobiomaterials - Grumezescu, Alexandru Mihai (Applications of nanobiomaterials ;, 2016)
Nanobiomaterials in Hard Tissue Engineering covers the latest developments in the field of hard tissue engineering at the nanoscale. Leading researchers from around the world discuss the latest research and offer new insights. This book presents data about the fabrication and characterization of nanobiomaterials involved in hard tissue reconstruction, describing recent progress and the advantages of both conventional and computer-aided methods. Recent applications of different classes of nanobiomaterials are discussed, with in vitro and in vivo applications also explained in detail. Special attention is paid to the applications of nanobiomaterials in bone regeneration and in the development of functional coatings for tailored implants to improve osseointegration. Finally, the book considers future challenges and perspectives. This book will be of interest to postdoctoral researchers, professors and students engaged in the fields of materials science, biotechnology and applied chemistry. It will also be highly valuable to those working in industry, including pharmaceutics and biotechnology companies, medical researchers, biomedical engineers and advanced clinicians.